Efektifitas Yoga Ketawa terhadap Penurunan Tekanan Darah pada Lansia dengan Hipertensi Derajat II di Panti Wredha Salib Putih Salatiga - Nehemia Bangkit Pangestu; Maria Dyah Kurniasari; Antonius Tri Wibowo (Jurnal Kesehatan, 2017)
Old age is often attacked the cardiovascular diseases such as hypertension. Ministry of Health Republic of Indonesia (2012) states that hypertension is one of the most influential risk factors for the incidence of heart disease and blood vessels. High blood pressure continuously increases the burden of the arteries slowly. The arteries undergo hardening process becomes thick and rigid, thus reducing its elasticity. Hypertension can also lead to heart disease because if high blood pressure is left without regular treatment, the heart must pump very strongly to push blood into the arteries, over time the walls of the heart muscle become thicker. An abnormally enlarged heart is an unhealthy heart because the heart becomes stiff and the beat tends to be irregular. This will make pumping less effective and eventually lead to heart failure. Pharmacologic treatment using drugs have the risk of side effects. The purpose of this study was to analyze the effectiveness of laughter yoga as non-pharmacological therapy in the elderly with hypertension by measuring the difference in blood pressure before and after being treated laughter yoga. Quantitative experimental research with pretest-posttest with a control group design. The sample used purposive sampling that is 20 elderly that is 10 elderly with treatment and 10 elderly as a control. The instrument was used analog tensimeter. Wilxocon different test results obtained from pre-treatment group of post systole and diastole p-value 0,007 and 0,003. While in control group of pre-post systole and diastole p-value 0,831 and 0,084. Laughter yoga effectively against decreased blood pressure in the elderly with grade 2 hypertension at the Panti Wredha Salib Putih Salatiga.